If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1n + 3n = 6n + 16 Combine like terms: -1n + 3n = 2n 2n = 6n + 16 Reorder the terms: 2n = 16 + 6n Solving 2n = 16 + 6n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-6n' to each side of the equation. 2n + -6n = 16 + 6n + -6n Combine like terms: 2n + -6n = -4n -4n = 16 + 6n + -6n Combine like terms: 6n + -6n = 0 -4n = 16 + 0 -4n = 16 Divide each side by '-4'. n = -4 Simplifying n = -4
| 3-2*-7=17 | | -2(y-3)=12 | | 2a^2+8a=-30 | | 12s^3t^3+3s^4t^2= | | 4=5x-24 | | x^2-5x-32=0 | | x=-2y-15 | | In(2x+1)-1=In(x-2) | | 2x^3+3x^2+36x=0 | | -(-2b^2+3)-b(2b-3)-3= | | 35(p-3)=-4 | | -14=10+3x | | -5x+4x+5=48 | | 4y+7=8y-5 | | -32-(-9)= | | 25s^3t^4+5s^4t^3= | | 2d^4=5d | | -9+6x=5x+12 | | (2x-13)+(x+41)+(x)=180 | | 5(5x-2)=-6(x+2) | | 9x=10x+90 | | -56+x=32+5x | | -(7c+18)-2c0= | | 2x+45=-9(x+6) | | -78+4x=42-8x | | -3(2x+4)+1=19 | | -8x-65=103+4x | | 60s=50 | | .03x+.4=8 | | -18-4x=16-6x | | -7x+11+2x=-4 | | -6x-8=13-7x |